Autism Spectrum Disorder: Comprehensive Understanding, Pharmacological Management and the Pharmacist Role: a literature review - Ximena Zenil Márquez; Josefina Reynoso Vázquez; Olga Rocío Flores Chávez; Beatriz Garnica Guerrero; Iracema Islas Vega; Pedro Rubén Negrete López; María Guadalupe Laura Báez Báez; Claudia Teresa Solano Pérez; David Pérez Becker; Jesús Carlos Ruvalcaba Ledezma (Public Health, 2026)
Autism Spectrum Disorder (ASD). This is a condition known as “Different Abilities.” is a neurodevelopmental disorder characterized by deficits in social communication, sensory processing alterations, and repetitive behaviors. Its global prevalence is estimated at 1 in 160 children, with a reported prevalence of 0.8% in Mexico. ASD is more commonly diagnosed in males, and prevalence data in Latin America are frequently underestimated due to socioeconomic barriers. As a multifactorial and highly heritable condition with a profound psychosocial impact that often triggers a grieving process within families, ASD requires an interdisciplinary approach in which behavioral interventions constitute the cornerstone of treatment, while pharmacological therapy serves as an off-label adjunct aimed exclusively at managing specific symptoms or comorbidities, such as Attention-Deficit/Hyperactivity Disorder (ADHD), epilepsy, and sleep disorders. Currently, only risperidone and aripiprazole have been approved by the U.S. Food and Drug Administration (FDA) for the treatment of irritability associated with ASD. Nevertheless, the clinical profile observed in the region indicates that more than 50% of pediatric patients are exposed to polypharmacy, increasing the risk of drug interactions and adverse effects, primarily metabolic and neurological and compromising treatment adherence due to resistance to change and sensory barriers commonly experienced by children. In this context, the pharmacist emerges as an essential member of the multidisciplinary team, playing a crucial role in ensuring pharmacotherapeutic follow-up, identifying and resolving medication-related problems, and providing health education to caregivers.